Spotlight on Learning from Failure : Fixing HealthCare.gov with Sha Hwang - Hwang, Sha (O'Reilly Media, Inc., 2019)
When Healthcare.gov officially launched on October 1, 2013, problems with the website were apparent immediately. High demand caused the site to go down within two hours of launch, and only six people were able to actually complete their applications on the first day. These issues were eventually addressed with the help of Nava, a public benefit corporation formed during efforts to help fix HealthCare.gov's troubled launch. Ultimately, over 1 million people successfully signed up for healthcare by the end of the open enrollment period. In this Spotlight on Learning from Failure , Sha Hwang, cofounder and COO of Nava, shares the stories behind scaling a company whose chief customer was one of the largest organizations on the planet: the United States government. You'll discover organizational, technical, and communication challenges Nava encountered-as well as best practices for building better foundations for culture, diversity, and impact-as you learn how this small team cut through mountains of red tape to transform a highly public debacle into well-oiled (and sustainable) machine. Recorded on August 27, 2019. See the original event page for resources for further learning or watch recordings of other past events . O'Reilly Spotlight explores emerging business and technology topics and ideas through a series of one-hour interactive events. In live conversations, participants share their questions and ideas while hearing the experts' unique perspectives, insights, fears, and predictions for the future. In every edition of Spotlight on Learning from Failure , you'll discover the lessons learned from failures both large and small. You'll discover how successful companies have addressed setbacks, missteps, and challenges and how you can grow from their examples.